Employment Volatility and the Sustainability of Payroll-Based Health Insurance Contributions in Indonesia: Evidence from the February 2025 National Labor Survey - Salma Khairunnisa; Antokalina Sari Verdiana (International Journal Labs, 2026)
This research examines the sustainability of payroll-based health insurance contributions in Indonesia using microdata from the February 2025 National Labor Force Survey (Sakernas). The analysis focuses on wage workers (pekerja penerima upah/PPU) as the main financing base of the National Health Insurance (JKN). The aim of this study is to analyze the sustainability of JKN financing, exploring factors such as income capacity, contribution coverage, job stability, employment contract structure, and job volatility, which affect the continuity of payroll-based contributions. Using cluster analysis and Principal Component Analysis (PCA), the study identifies three major labor-risk segments among PPU workers: formal and stable, semi-formal, and vulnerable or volatile. The findings show that the vulnerable or volatile group constitutes the largest share of the PPU population and exhibits the highest stopwork rate, making it the primary source of national risk to the sustainability of payroll-based contributions. In contrast, the formal and stable group presents the lowest risk, while the semi-formal group represents a smaller transitional segment with relatively high employment disruption. The sustainability of JKN financing depends not only on workers' ability to pay contributions but also on the stability of employment relationships and labor market dynamics. Policies aimed at strengthening employment continuity, reducing contract-related job disruption, and protecting high-risk sectors and regions are essential for maintaining JKN membership and contribution flows.